Studies on integrated management of vascular wilt disease of chickpea crop caused by Fusarium oxysporum f. sp. ciceri through fungal biocontrol agents, Glomus fasciculatum, Bacillus subtilis and fungicides - PANDEY, RAJESH KUMAR (Indian Phytopathology, 2016)
Bundelkhand (BKD) region in central plains of India comprises of 13 districts covering a total area of 7.08 m ha, out of which six districts with 4.12 m ha area are in Madhya Pradesh (MP) and seven districts with 2.94 m ha area in Uttar Pradesh (UP). The districts are: Sagar, Damoh, Datia, Panna, Chhatarpur, and Tikamgarh in MP and Jhansi, Lalitpur, Jalaun, Hamirpur, Banda, Mahoba and Chitrakoot in UP. These districts lag behind in terms of development but hold tremendous potential for pulses in terms of productivity improvement. Rabi pulses account for 62-69% of the net sown area under total pulses in BKD and the remaining 31-38% area is under kharif pulses. Lentil, chickpea and field pea are the popular rabi crops in BKD and presently occupy 323,000 ha, 826,000 ha and 528,000 ha area with annual production of over 210,000 tons, 651,000 tons, and 405,000 tons, respectively. However, BKD remains a low productivity zone compared to other parts of UP and MP. This is mainly because majority of the farmers still facing a variety of problem in form of biotic constraints/factors. Among the major biotic constraints, vascular wilt causing fungal pathogen Fusarium oxysporum f. sp. ciceri is considered one of the major limiting factors for productivity of Chickpea (Cicer arietinum L.). In present study a microplot experimental trial was conducted for the management of vascular wilt causing fungal pathogen F. oxysporum f. sp. ciceri infecting chickpea through talc based formulation of antagonistic fungal biocontrol agents viz. Trichoderma harzianum (Indian Type Culture Collection No.-6797), T. viride (ITCC No.-2109), T. virens (ITCC No.-4177) alone and in integration with Glomus fasciculatum, Bacillus subtilis, Carbendazim 50% WP and Thiram. Field experiments were conducted in a randomized block design with sixteen treatments (viz. T-1 = Trichoderma harzianum, T-2 = T. viride, T-3 = T. virens, T-4 = T. harzianum + G. fasciculatum, T-5 = T. harzianum + B. subtilis, T-6 = T. harzianum + Carbendazim 50% WP, T-7 = T. harzianum + Thiram, T-8 = T. viride + G. fasciculatum, T-9 = T. viride + B. subtilis, T-10 = T. viride + Carbendazim 50% WP, T-11 = T. viride + Thiram, T-12 = T. virens + G. fasciculatum, T-13 = T. virens + B. subtilis, T-14 = T. virens + Carbendazim 50% WP, T-15 = T. virens + thiram T-16 = control) including control along with three replications on sick plot of wilt causing pathogen at Bundelkhand University, Jhansi during Rabi 2013 and 2014. Both seed (talc based formulations of biocontrol agents and fungicides) and soil (G. fasciculatum) treatments has been given at the time of sowing of chickpea seeds (Cv JG-62) with spacing of 15x30 cm. Seed germination and reduction of disease incidences has been recorded and statistically analyzed for every treatment. Among all the treatments, T. harzianum + G. fasciculatum, T. viride + G. fasciculatum, T. virens + G. fasciculatum were found most effective and significantly at par for improving the germination percent (55.13-86.70%) along with suppressing disease incidences as compared to all other treatments including control.